INDUSTRIALISASI TRADISI SHALAWATAN, DARI DAKWAH MENUJU KOMODITAS - Fuad, Mohammad Zuhurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to look at the phenomenon of reading prayers in the Az-Zahir prayer group. Shalawat, which previously had the value of worship, is slowly turning into an activity that has the value of profit. The main question in this research is